Quality assessment of escaping silver eel (Anguilla anguilla L.) to support management and conservation strategies in Mediterranean coastal lagoons - Capoccioni F.; Leone C.; Belpaire C.; Malarvannan G.; Poma G.; De Matteis G.; Tancioni L.; Conto M.; Failla S.; Covaci A.; Ciccotti E. (Environmental Monitoring and Assessment, 2020)
Silver eel samples, collected from the lagoons of Fogliano and Caprolace (Italy), were investigated for a broad range of contaminants (29 polychlorinated biphenyls, 9 polybrominated diphenyl ethers, 5 dichlorodiphenyltrichloroethane, 5 chlordanes, hexachlorobenzene, 3 hexachlorocyclohexane, and 5 metals). Concentrations of targeted compounds stand for a general low contamination pattern. Infestation byAnguillicola crassusand virus infections were also examined. No parasite infestation was found, while infected silver eels had a low prevalence for EVEX, and, for the first time in the Mediterranean area, for AngHV-1. Overall, a good quality status of escaping silver eels, for both lagoons, was highlighted by the use of integrative Indexes. A quality assessment of the ecological status of the two lagoons was carried out developing an expert judgment approach, in order to characterize the habitat of eel stocks. A Final Pressure Index was derived, whose values showed an overall limited global anthropogenic impact acting on both lagoons. Results stand for the suitability of an integrated approach to assess lagoon habitats and eel local stocks quality. This could be proposed as a tool to identify sites yielding high quality eel spawners in the Mediterranean region, in order to set up suitable management frameworks, providing elements to appraise and discuss the potential of coastal lagoons in the Mediterranean region towards the recovery of the eel global stock.